The effect of resveratrol on the viability of rat bone marrow mesenchymal stem cells - Fatemeh Ghasemi; RozaSadat RezaTofighi; Mohammad Moradiani Moradabadi; Mona Zamanpour; Michael Aghcheli; Mohammad Amin Ebrahimi; Ali Khatib; Fatemeh Ashabi (Clinical Nutrition Open Science)
Summary: Background and aim: Resveratrol is a plant polyphenol that has antioxidant properties. In this research, in order to better understand the role of resveratrol on bone, the effect of different doses of resveratrol on the viability, proliferation, differentiation and biochemical factors of rat bone marrow mesenchyme stem cells (MSCs) was investigated. Methods: To evaluate the ability of proliferation and differentiation, the MSCs were cultured up to three passages and were placed in culture media without osteogenic stimulation. At first to investigation the proliferation ability, the viability was evaluated by MTT test and trypan blue staining with 7.5, 15 and 30 mg/L treatment doses after 12, 24 and 36 hours. Then, to investigation the differentiation ability, the effect of 7.5, 15, and 30 mg/L treatment doses was assessed on the viability, electrolyte levels, and the activity of LDH, AST, ALP and ALT enzymes in differentiated cells after 5, 10, 15, and 21 days. To investigation the differentiation ability, the effect of 7.5, 15, and 30 mg/L treatment doses was assessed on the viability, electrolyte levels, and the activity of Lactate dehydrogenase (LDH), Aspartate aminotransferase (AST), Alkaline phosphatase (ALP) and alanine aminotransferase (ALT) enzymes in differentiated cells after 5, 10, 15, and 21 days. The data were analyzed by ANOVA and Tukey's test, and p<0.05 was considered as a significant level. Results: The obtained results showed that in mesenchyme cells, the level of viability does not change in low dose of resveratrol, however increase in the time followed by decrease in the activity of metabolic enzymes (ALP, ALT and AST P<0.5) and subsequently viability (p<0.05), and this trend was reversed with increasing resveratrol concentration (significant differences among 5 days and others). Conclusion: The effect of resveratrol depends on the type of cell and the treatment conditions, so it was shown in this study that the sensitivity of mesenchymal cells is higher than that of osteoblast cells. In addition, high doses of resveratrol had a positive effect on bone differentiation, so high doses of resveratrol can have a beneficial role on the health of mesenchymal cells and their differentiation into osteoblasts.